A systematic review on prognostic indicators of acute on chronic liver failure and their predictive value for mortality. (19th March 2012) - Wlodzimirow, Kama A.; Eslami, Saeid; Abu‐Hanna, Ameen; Nieuwoudt, Martin; Chamuleau, Robert A. F. M.
Abstract Background An early and proper diagnosis of acute on chronic liver failure (ACLF), together with the identification of indicators associated with disease severity is critical for outcome prediction and therapy. Objective To systematically identify and summarize prognostic indicators for patients with ACLF and to evaluate the predictive value of these indicators. Methods Embase and Ovid‐Medline were searched for English‐language articles. The search criteria focused on identifying clinical trials and observational studies reporting on indicators used for prediction of mortality in patients with ACLF. Results Of 2382 studies identified, 19 were included for detailed analysis. Thirteen different definitions of ACLF were found. The main differences were related to acute deterioration in liver function, coagulopathy and hyperbilirubinaemia/jaundice. Seventy three prognostic indicators and their association with mortality were extracted and categorized into seven categories: general markers (n = 13), viral markers (n = 6), bio‐markers (n = 22), hemodynamics (n = 1), morphology/histology (n = 17), scoring systems (n = 10) and treatments (n = 4). Conclusions The ambiguity and variability in the definition of ACLF and in its predictive indicators hampers comparability among studies. There is a need for a single uniform definition of ACLF. Also absence of a gold standard is an obstacle to render one indicator superior to another. The age, hepatic encephalopathy, model for end‐stage liver disease score, total bilirubin and International normalized ratio (prothrombin time) appeared to be promising candidates for evaluation in future studies. The result of this review may be useful as a starting point in developing a standard list of indicators for clinical outcome that concur with the clinicians' subjective views on prognosis in ACLF.